ROLE OF PAX-5 TRANSCRIPTION FACTOR IN IMMUNOLOGICAL PROCESSES - V. N. Mineev (SPb RAACI, 2014)
Abstract.  The  review  article  concerns  various  features  of  PAX-5  (paired  box  5)  transcription  factor,  its structure, functions, regulation of activity, involvement into differentiation and activation of B lymphocytes, switching to IgE synthesis, its role in oncogenesis, and a putative role of this factor for development of bronchial asthma.Further  insight  into  specific  properties  of  PAX-5  factor  in  bronchial  asthma  may  provide  a  promising approach to studying mechanisms of this disorder. (Med. Immunol., 2011, vol. 13, N 6, pp 569-580)